2020
DOI: 10.3390/su12208658
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Feeding Schedule on the Growth Performances of Tilapia, Common Carp, and Rice Yield in an Integrated Rice-Fish Farming System

Abstract: Feeding frequency, among various factors, greatly influences the production costs of aquaculture. In the present investigation, the effects of feeding schedule on the growth and production of tilapia and common carp were evaluated, along with rice yield, in an integrated rice-fish culture system. The experiment comprised 11 treatments, each with three replications, and a control treatment with no fish (T0). The fish in treatments T1–T5 were fed with rice bran once per week at 09:00 for T1, two days per week at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…For faro 44, the yield of rice, plant height, seed quantity, and leaf count were all high; this may be attributed to nutrient enrichment, availability, and a favorable environment for growth, as demonstrated by the current study. These are similar to the findings of [14], who claimed that high nutrient availability can be used to explain rice and fish growth performance in integrated rice fish farming. The fish can also obtain food from the surrounding environment, such as earthworms, planktons, insects, and young tilapia species, in addition to the feed that is provided.…”
Section: Resultssupporting
confidence: 89%
“…For faro 44, the yield of rice, plant height, seed quantity, and leaf count were all high; this may be attributed to nutrient enrichment, availability, and a favorable environment for growth, as demonstrated by the current study. These are similar to the findings of [14], who claimed that high nutrient availability can be used to explain rice and fish growth performance in integrated rice fish farming. The fish can also obtain food from the surrounding environment, such as earthworms, planktons, insects, and young tilapia species, in addition to the feed that is provided.…”
Section: Resultssupporting
confidence: 89%
“…Feeding with artificial feed and the availability of natural food due to the use of organic fertilizer significantly improved the relative and specific growth rates of the farmed fish, especially in the first periods of the experiment from 14-56 days, this indicates that the nutritional needs of fish are not met by natural food only, but rather by supplemental feeding, especially in the early stages of growth of farmed fish.The resulting growth in rice fields that were not provided with any supplementary feed is attributed to the availability of natural food, and this applies to T1 and T4. Boyd (7) indicated that there is a strong positive relationship between fish growth and primary productivity in the fertilized ponds without the use of supplementary food.The study of Billah et al (6) showed that feeding with artificial floating feed significantly affected the weight gain and relative growth rate of common carp fish compared to feeding with conventional feed (rice bran). Priyadarshini et al (23) conducted a study on the culture of common carp in ponds of 25 m 2 , using four treatments (the first treatment: without feeding and adding fertilizer, the second treatment: adding poultry manure fertilizer at a rate of 2000 kg/ha at the beginning of the experiment and then adding 200 kg/ha).…”
Section: Relative and Specific Growth Ratementioning
confidence: 99%
“…2 As a typical integrated agricultural-aquaculture system, rice field farming activities include rice tilapia, rice carp, rice crayfish, and rice-turtle. 1,3,4 However, the risk assessment indicated that the exposure to toxic levels of pesticides for aquaculture is significant, at least shortly after pesticide application. 5 Less research has been done in rice field habitats, particularly in rice-crayfish culture systems without artificial diets for crayfish.…”
Section: Introductionmentioning
confidence: 99%